2021
DOI: 10.3390/molecules26020449
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Quaternized Aminated Chitosan Nanoparticles for Efficient Encapsulation and Slow Release of Curcumin

Abstract: An effective drug nanocarrier was developed on the basis of a quaternized aminated chitosan (Q-AmCs) derivative for the efficient encapsulation and slow release of the curcumin (Cur)-drug. A simple ionic gelation method was conducted to formulate Q-AmCs nanoparticles (NPs), using different ratios of sodium tripolyphosphate (TPP) as an ionic crosslinker. Various characterization tools were employed to investigate the structure, surface morphology, and thermal properties of the formulated nanoparticles. The form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 51 publications
(59 reference statements)
3
30
0
Order By: Relevance
“…On the other hand, the observed absorption bands around 1016 cm −1 in the QAMCS spectra could be attributed to the stretching vibration of C–N in the quaternary ammonium groups. In addition, the peaks at around 1385–1393 cm −1 are associated with the C-H symmetric bending of the methyl groups in the generated quaternary ammonium groups [ 26 , 50 ]. Moreover, the peak intensities were amplified with the increase of the quaternization ratio in the membrane matrix, as evidence of the successful preparation process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the observed absorption bands around 1016 cm −1 in the QAMCS spectra could be attributed to the stretching vibration of C–N in the quaternary ammonium groups. In addition, the peaks at around 1385–1393 cm −1 are associated with the C-H symmetric bending of the methyl groups in the generated quaternary ammonium groups [ 26 , 50 ]. Moreover, the peak intensities were amplified with the increase of the quaternization ratio in the membrane matrix, as evidence of the successful preparation process.…”
Section: Resultsmentioning
confidence: 99%
“…The quaternization process was conducted according to the authors’ reported study [ 26 ], with a minor modification. Briefly, AMCS (1 g) and NaI (4.8 g; as a catalyst) were placed in a 2-necked flask containing 80 mL of an N-methyl-2-pyrrolidinone/acetic acid (1%) mixture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro drug release study in various physiological media (simulate gastric fluid, pH = 1.2; and simulated colon fluid, pH = 7.4) exhibited controlled cumulative drug release in alkaline pH (74%). The NPs depicted acceptable biocompatibility and biodegradability that suggested potential use for cancer management [ 141 ]. Improved solubility of quaternized chitosan in variable pH ranges encourages versatile biomedical usage [ 142 ].…”
Section: Biomedical Applications Of Quaternized Chitosan Derivativesmentioning
confidence: 99%
“…Quaternized chitosans as cationic modified scaffolds have extraordinary features in drug delivery approaches. Omer et al (19) reported nanoparticles-based quaternized aminated chitosan for curcumin delivery. Another study was conducted by Yang et al (20) on N-[(2-Hydroxyl)-propyl-3-trimethyl ammonium chitosan chloride (HTCC) as a drug carrier for cyclosporine A. Trimethylated chitosan nanoparticles are the most common studied cationic modified chitosan with significant statistics of articles in the field of drug and gene delivery (21).…”
Section: Introductionmentioning
confidence: 99%